Clinical motivation for 31P MRS studies on the myocardial energy metabolism of brain dead cats. Issue 2 (2003) - Bruinsma Bruinsma, G. J. Brandon Bravo G. J. Brandon Bravo; Echteld Echteld, C. J. A. Van C. J. A. Van
Abstract : Hemodynamic instability of the brain dead potential heart donor is an exclusion criterion for heart donation for transplantation. Based on the results of myocardial biopsies it has been reported that brain death-related catecholamine induced damage of the heart causes depletion of high-energy phosphates which could explain contractile dysfunction. Our group has shown in a series of 31 P MRS experiments in cats that neither the onset of brain death, nor the hemodynamic deterioration which follows, nor its treatment with high dosages of dopamine affect the heart energetically as expressed by PCr/ATP ratios. However, after cardioplegic arrest and explantation, an initial and prolonged lower ATP content and an anomalous higher PCr/ATP ratio in the brain death group was found when compared with controls during long-term unperfused cold storage of the hearts. During subsequent reperfusion of the hearts, ATP and PCr levels in the brain death group were lower than in controls but equal partial recovery of PCr/ATP ratios was observed in both groups. It was concluded that PCr/ATP ratios need to be interpreted with great caution. Secondly, brain death-related hemodynamic instability is not related to significant changes of myocardial energy metabolism. Thirdly, brain death does affect the myocardial energy metabolism but the impact became apparent only during hypothermic storage and subsequent reperfusion of the donor heart.